Organization of Community-Based Respirator Fit Testing Programs for Agricultural Workers. - Gibbs, Jenna Leigh; Sheridan, Carolyn E.; Duysen, Ellen; Danielson, Elizabeth; Tutor, Robin; Anthony, T. Renee (Workplace Health & Safety, 2026)
Background: The agricultural industry exposes individuals to diverse respiratory hazards, yet historically, respirator use has been low. Ensuring proper protection remains challenging due to complex agricultural hazards (e.g., pesticides, dust, zoonotic diseases, wildfire smoke) and limited rural access to health care services. This professional practice publication outlines the development and initial impact of Community-Based Respirator Fit Testing Programs, highlighting the vital roles of nurses and community collaboration. Methods: This publication draws upon over 40 years of combined experience from a multidisciplinary team in conducting Community-Based Respirator Fit Testing workshops. It synthesizes insights from eight workshops over 5 years, engaging 175 participants across five states. These workshops trained diverse agricultural safety stakeholders on requirements for the Occupational Safety and Health Administration (OSHA), respiratory exposures, qualitative fit testing principles, and fit tester responsibilities, informed by two comprehensive Respirator Fit Test Guides developed in collaboration with National Institute for Occupational Safety and Health (NIOSH)-funded Agricultural Health and Safety Centers. Findings: Community-Based Respirator Fit Testing Programs require multiple steps, including on-farm hazard identification, appropriate respirator selection (considering cost challenges), medical evaluation, annual fit testing, training, and documentation. Discussion: Major challenges to fit test programs in rural agricultural areas include the cost of equipment and limited healthcare provider engagement. The most significant barriers identified during workshops were community awareness about respiratory protection and distance to services. These are compounded by agriculture's time-sensitive nature which favors task-based guidance. Conclusion: Respiratory protection is vital for agricultural health. While self-reported use has increased in recent years, proper implementation through Community-Based Respirator Fit Testing Programs is crucial.